Penentuan Faktor Pengelolaan Tambak yang Mempengaruhi Produktivitas Tambak Kabupaten Mamuju, Provinsi Sulawesi Barat [Determining Of Brackishwater Pond Management Factors That Effect On The Brackishwater Pond Productivity In Mamuju Regency, West Sulawesi Province] - Akhmad Mustafa; Erna Ratnawati; Irmawati Sapo (Faculty of Fisheries and Marine Universitas Airlangga, 2010)
Abstract One of regency in West Sulawesi Province that has vast area of brackishwater ponds is Mamuju Regency. However, there is not yet information on pond management that conducted by farmers in Mamuju Regency. Hence, it was carried out a research that aim to know pond management factors that effect on the pond productivity in Mamuju Regency. Survey method that applied to find primary data and ponds production also pond management by means of questionnaires. The dependent variable in this research was total production, while the independent variables were pond management factors that consists of 30 variables. Multiple regressions with dummy variable were used to analyze the data in predicting total production. The results show that total production of brackishwater ponds in Mamuju Regency is 349.5 kg/ha/season in average. There are seven pond management variables that effect on total production in Mamuju Regency i.e. stocking density of milkfish, stocking density of tiger prawn, out-break disease, initial liming, duration of milkfish culture, initial pest control with teaseed and size of tiger prawn that stocked in the brackihswater pond. The total productivity of brackishwater pond can be increase through increasing dosage of initial liming, increasing duration of milkfish culture, increasing dosage of teaseed as initial pest control as well as increasing size of tiger prawn that stocked in the brackishwater ponds.